2021
DOI: 10.1007/s40122-021-00252-1
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Noninvasive Brain Stimulation for Neuropathic Pain Patients: A Systematic Review

Abstract: Introduction: The objective of this review is to systematically summarize the consensus on best practices for different NP conditions of the two most commonly utilized noninvasive brain stimulation (NIBS) technologies, repetitive transcranial magnetic stimulation (rTMS), and transcranial direct current stimulation (tDCS). Methods: PubMed was searched according to the predetermined keywords and criteria. Only English language studies and studies published up to January 31, 2020 were taken into consideration. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 60%
“…Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ). Even less clinical study has been done on the application of rTMS in patients with cancer pain.…”
Section: Introductionmentioning
confidence: 99%
“…After 1–2 months of follow-up (161 participants), the analgesic effects of multiple rTMS treatments (≥5 sessions) were observed to last at least 1 month but not more than 2 months, indicating that the different analgesic effects of rTMS may depend on the neuroanatomical source of the pathophysia of NP, that is, the more effective source of the therapeutic effects of rTMS on NP is the “top” (supraspinal, cranial, or spinal) rather than the “bottom” (nerve roots or peripheral nerves). Similarly, Zhang et al (2021) systematically reviewed 29 studies (24 for rTMS, 736 participants), and found that rTMS successfully improved the pain symptoms of 97.1% of patients with NP (715 participants). The analgesic effect of rTMS was maintained for 2 weeks after the last session, but this beneficial effect usually lasted for less than 1 month.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…According to the anatomical location of the injury or disease, NP can be classified as central NP (CNP), which is due to lesions or diseases of the spinal cord or brain, and peripheral neuropathic pain (PNP), which includes diabetic neuropathy, nerve damage, facial pain, phantom limb pain, cancer pain, and deformity ( Colloca et al, 2017 ). The most common CNP syndromes include NP associated with spinal cord injury (SCI), post-stroke pain (PSP), NP associated with multiple sclerosis (MS), and Parkinson’s disease (PD) ( Finnerup et al, 2016 ; Zhang et al, 2021 ; Figure 1 ). The appearance and aggravation of pain symptoms often occur within a few days after the lesion or disease.…”
Section: Introductionmentioning
confidence: 99%